THE RELATIONSHIP BETWEEN THE LEVELS OF SERUM CALICIUM AND EVIDENCE DYSTOCIA IN EWES - Mohammed A. Al-Safi; Taher A. Fahed (Basrah Journal of Veterinary Research)
The present study was carried out in ewes to investigate the causes of dystocia andeconomic effect, reared in Basrah governorate (Basra – Iraq ) .The current study was started from August 2017 to May 2018 , and conductedon 60 ewes,1.5-10 years old. Animals were divided into two groups,First treated group: 40 ewes suffered from dystocia. and theSecond normal group: 20 ewes with normal parturition served as a healthy control.Ewes with dystocia were diagnosed on the bases of clinical inspection .The study showed that the ewes that suffered from dystocia have a low serumlevel of calcium compared with control group.